Fagspråk og koding i tre norskordbøker fra Kunnskapsforlaget - Eek, Øystein (LexicoNordica, 2018)
Systematic labelling of field-specific headwords, definitions and examples in general dictionaries is useful for editorial purposes, but probably also useful for most users of dictionaries. The article discusses the labelling technique in three Norwegian monolingual dictionaries, and argues in favour of a wider use of labelling in metadata and also in the lexicographical texts themselves. The systematization of articles in encyclopedias is a possible source. The article also suggests a Nordic or Scandinavian joint effort in order to achieve best practice and exchange of updates.